Does Knowing Your FICO Score Change Financial Behavior? Evidence from a Field Experiment with Student Loan Borrowers - Homonoff, Tatiana; O'Brien, Rourke; Sussman, Abigail B. (The Review of Economics and Statistics, 2021)
Abstract One in five consumer credit accounts incurs late fees each quarter. Evidence on the efficacy of regulations to improve behavior through enhanced disclosure of financial product attributes is mixed. We test a novel form of disclosure that provides borrowers with a personalized measure of their creditworthiness. In a field experiment with over 400,000 student loan borrowers, treatment group members received communications about the availability of their FICO Score. The intervention significantly reduced late payments and increased borrowers' FICO Scores. Survey data show treatment group members were less likely to overestimate their FICO Scores, suggesting the intervention may correct for overoptimism.